BSCI-03 THE ROLE OF LONP1 IN DRIVING ENHANCED PMT IN THE 'LEADING EDGE' NICHE IN GLIOBLASTOMA. (5th August 2022) - Douglas, Christopher; Lomeli, Naomi; Bota, Daniela
Abstract: Glioblastoma (GBM), a high grade brain tumor, possesses poor overall survival with less than 5% surviving past five years. Previously, the TCGA classifications for GBM have included the mesenchymal, proneural, classical and neural subtypes with their own respective expression profiles and survival. Recent omics analysis has revealed other key aspects of GBM pathology, including intratumoral heterogeneity spanning all subtypes and enhanced stemness and treatment resistance and other hallmarks of proneural mesenchymal transition (PMT) following treatment with first-line standard of care treatment with radiation therapy and temozolomide (TMZ). Invading glioma stem cells (GSC) with high Nestin and hypoxia-inducible factor 1 alpha (HIF-1α) expression have been theorized to contribute to recurrence. HIF-1α acts as a master regulator driving increased stemness, invasiveness and angiogenesis. Interestingly, HIF-1α and nuclear respiratory factor-2 both upregulate Lon peptidase 1 (LonP1) in response to increased hypoxia or reactive oxygen species (ROS) production. LonP1 has been shown to drive increased metastasis, tumor growth and epithelial-mesenchymal transition (EMT), an analog of PMT, in colon cancer, melanoma and other cancer types. In a recently elucidated GBM organoid model, we present new findings demonstrating the importance of LonP1 in driving enhanced, transient PMT near the 'invading edge'. This includes the enhanced expression of several key drivers of PMT and phenotypic hallmarks, such as increased invasiveness, proliferation and poorer survival.